METHOD AND PRINCIPLE OF MARITIME BOUNDARY DELIMITATION BETWEEN STATES WITH OPPOSITE OR ADJACENT COASTS (CASE OF INDONESIA AND TIMOR-LESTE) - Jaya, Belardo Prasetya Mega; Cahyani, Ferina Ardhi; Idris, Idris; Permata, Rika Ratna (Fakultas Hukum, Universitas Diponegoro, 2022)
In the practice the maritime boundary delimitations can cause the overlap of claims between states with opposite or adjacent coasts. Regarding the maritime boundary between Indonesia and Timor-Leste, there was never a maritime boundary between both States, so it needs a settlement of disputes of maritime boundary delimitation between both parties. Therefore, these research aims to explain the methods and principles that could be used in resolving maritime boundary delimitation dispute between state with opposite or adjacent coasts based on international law and analyze how obstacles and solution to solve maritime boundary delimitation dispute between Indonesia and Timor-Leste (East Timor). This research uses normative legal research and Empirical Research Methods. The results of the research show that: (1) the maritime boundary delimitation between Indonesia and Timor-Leste uses enclaving, equidistant, and three-step approach method. (2), Indonesia and Timor Leste have the potential to determine maritime boundaries in the three areas, namely the area to the north of the Oecusse (Ombai Strait), to the north of Timor Island (Wetar Strait) and to the south of Timor Island (Timor Sea). Timor-Leste will still get a maritime territory in District Oecusse but the extent would be negotiated with Indonesia first, while in the Wetar Strait, the territorial sea division of the two countries would consider the outer islands of both countries.